S4 Pulmonary Artery Pressure and Exercise Tolerance in Patients with Pulmonary Arteriovenous Malformations. (12th November 2015) - Hall, T; Tighe, H; Hornby, K; Park, M; Santhirapala, V; Murphy, K; Jackson, JE; Howard, L; Shovlin, CL
Abstract : Introduction and objectives: Pulmonary arteriovenous malformations (PAVMs) provide direct communications between pulmonary arteries and pulmonary veins, bypassing the pulmonary capillary bed. Greater improvements in exercise capacity following embolization therapy have been reported by PAVM patients with raised pulmonary artery pressures (PAPs). The objective of this study was to test the hypothesis that lower PAPs are associated with greater exercise capacity in hypoxaemic PAVM patients. Methods: Patients attending our tertiary care institution were recruited at the time of PAVM assessment or embolization. Pulmonary artery pressure measurements were obtained by right-heart catheterisation immediately prior to contrast injection and embolization. For both patients and healthy controls, incremental cardiopulmonary exercise tests were performed seated on an adjustable cycle ergometer (MasterScreen CPX; Via Sprint). Results: A total of 19 patients and 26 controls were recruited for the study. Significantly lower arterial oxygen saturations (median 91% vs. 98%, p < 0.0001) and end-tidal PCO2 levels were demonstrated in patients alongside significantly raised V[dot]e/V[dot]CO2 slopes (32.2 vs. 24.1 L/min/L/min, p = 0.0003). The regression models that best described peak oxygen uptake (V[dot]O2 ) as a percent of predicted values, were similar between PAVM patients and controls. Surprisingly, despite the differences in SaO2 between PAVM and control subjects, the addition of SaO2 to the final models did not improve the significance of the final model nor did it raise the adjusted-r 2 value. For the PAVM subgroup, the median mean PAP was 14.5 mmHg, (IQR 12.5–16.0; range 6–22). Univariate and multiple regression analyses demonstrated no significant relationships between systolic, diastolic or mean PAPs, and peak exercise parameters. Conclusions: This study has demonstrated in a population of PAVM patients with hypoxaemia and PAPs essentially within the normal range, that PAP does not have a major influence on peak exercise capacity.